Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1103/physrevb.84.235210
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast relaxation of highly excited hot electrons in Si: Roles of theLXintervalley scattering

Abstract: Two-photon photoemission (2PPE) spectroscopy is used to reveal dynamic relaxation of highly excited electrons generated by 3 eV photons in Si. Monochromatic 2PPE at probe-photon energies ranging from 3.2 to 3.5 eV reveals a coherent 2PPE peak from the valence band maximum, and a transiently populated photoemission peak near L 1 in the conduction band. Time-resolved 2PPE measurements show that electrons injected into the L valley undergo L-to-X intervalley scattering with a time constant of 180 fs at 293 K. A d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
53
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 42 publications
9
53
0
Order By: Relevance
“…In indirect gap semiconductors, however, the situation is more complicated because most of the photoexcited electrons undergo intervalley scattering and populate different satellite valleys at different times. For Si, previous studies [55,56] revealed that the electrons excited at the L valley are scattered into the X valley, as illustrated in Fig. 2b, with a time constant of 0.2−0.5 ps.…”
Section: Discussionmentioning
confidence: 92%
“…In indirect gap semiconductors, however, the situation is more complicated because most of the photoexcited electrons undergo intervalley scattering and populate different satellite valleys at different times. For Si, previous studies [55,56] revealed that the electrons excited at the L valley are scattered into the X valley, as illustrated in Fig. 2b, with a time constant of 0.2−0.5 ps.…”
Section: Discussionmentioning
confidence: 92%
“…The STL threshold found here of +2 V therefore suggests that if the same electron dynamics occur, then the light emission for injections above +2 V would be from the bottom of the U 3 state. We therefore propose that after the injected electron has undergone diffusion for 200 fs [36], it decays out of the state and may emit a photon, or manipulate a molecule. Therefore there are at least 3 decay channels: one leading to manipulation, one leading to light emission, and one that is inactive.…”
Section: Discussionmentioning
confidence: 99%
“…We take τ D =200 fs [36] and so convert the β values of figure 4 to the total probability of manipulation per injected electron N as displayed in figure 5(c). This form of analysis should be identical to the original 'scanning' manipulation work and indeed we find our results here match qualitatively and quantitatively with that earlier work [32,39].…”
Section: Discussionmentioning
confidence: 99%
“…symmetry point (the smallest direct band gap), so interband transitions (process 1) result in electrons in the Lvalley. Then electrons undergo L-X intervalley scattering (process 2) with a time constant of 180 fs [28]. The electron distribution is thermally equilibrated with the lattice via phonon scattering within less than 2 ps [28][29][30].…”
mentioning
confidence: 99%